Cellulose-based bioengineering plastic, reversible shaping cellulose-based bioengineering plastic, and preparation method and application of cellulose-based bioengineering plastic and reversible shaping cellulose-based bioengineering plastic

By using formic acid-zinc chloride solution and metal ion-induced self-assembly technology in cellulose-based bioplastics, combined with acrylamide polymerization, the solubility of cellulose-polyacrylamide supramolecular gel is solved, and the solubility of cellulose-based bioplastics is solved. and processability issues, the preparation of cellulose-based bioengineered plastics with lightweight, high strength and strong thermal stability is achieved to meet high performance needs.

CN119264331APending Publication Date: 2025-01-07NORTHEAST FORESTRY UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411622857.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The solubility and processability of existing cellulose-based bioplastics are limited, the modification process is high and easy to degrade, resulting in insufficient mechanical properties and thermal stability, making it difficult to meet the use requirements of high-performance plastics.

Method used

Cellulose is dissolved by mixed aqueous solution of formic acid-zinc chloride, and self-assembly is induced by metal ions to form a cellulose formate hydrogel framework, and polymerize it with acrylamide to form a cellulose-polyacrylamide supramolecular gel, using organic Solvent controls the molecular configuration and prepares lightweight, high-strength, and strong thermal stability cellulose-based bioengineering plastics.

Benefits of technology

It has achieved the preparation of high-performance cellulose-based bioengineered plastics under mild conditions, with good moldability and repeatable shaping ability, significantly improving the application potential of cellulose-based bioplastics, meeting the needs of engineering plastics, and reducing energy consumption and carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264331A_ABST
    Figure CN119264331A_ABST
Patent Text Reader

Abstract

The invention provides cellulose-based bioengineering plastic, reversible shaping cellulose-based bioengineering plastic and a preparation method and application thereof, and relates to the technical field of engineering materials. Cellulose is dissolved in a formic acid-zinc chloride mixed aqueous solution and esterified to form a cellulose formate solution, and after a metal ion source solution is added, cellulose formate effectively promotes self-assembly of cellulose molecules under induction of metal ions to form a cellulose formate hydrogel skeleton; the preparation method comprises the following steps: immersing a cellulose formate hydrogel skeleton into an acrylamide aqueous solution for replacement and in-situ polymerization to form cellulose-polyacrylamide supramolecular network hydrogel, carrying out replacement shaping with an organic solvent, regulating and controlling the supramolecular network configuration, and drying to obtain the cellulose-based bioengineering plastic with light weight, high strength, excellent thermal stability and degradability. And after water plasticizing, replacing and shaping with an organic solvent again, so that the cellulose-based bioengineering plastic can be reversibly processed and shaped for multiple times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials, and in particular to a cellulose-based bioengineering plastic and a preparation method and application thereof, and a reversibly shaped cellulose-based bioengineering plastic and a preparation method and application thereof. Background Art

[0002] Cellulose is the world's most abundant biomass resource with excellent physical and chemical properties. It is a potential substitute for petroleum-based plastics. The rich hydroxyl groups in cellulose molecules give cellulose high chemical reactivity, but due to the large number of hydrogen bonds within and between molecular chains, these hydrogen bonds form a highly ordered crystalline structure, which greatly limits the solubility and processability of cellulose. It is necessary to chemically modify cellulose to make it soluble in common solvents or adjust its thermoplasticity to meet thermal processing conditions. Common modification methods include acetic acid esterification, propionic acid esterification and butyric acid esterification. However, the modification process requires the use of expensive reagents and special processes and equipment, which increases the production cost. In addition, the modified cellulose plastic is easily degraded during processing, and it is difficult to ensure high-strength mechanical properties and thermal stability, which limits its application.

[0003] The prior art discloses that cellulose can be used to develop cellulose-based bioengineering plastics by dissolving and regenerating cellulose using solvents such as ionic liquids (e.g., [Bmim]Cl ionic liquids), lithium chloride / N,N-dimethylacetamide, and alkali / urea systems. However, the regenerated cellulose network obtained using the above solvents lacks good molecular design and regulation, resulting in poor mechanical properties of the prepared cellulose bioengineering plastics, making it difficult to meet the use requirements of high-performance plastics. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a cellulose-based bioengineering plastic and a preparation method and application thereof, a reversibly shaped cellulose-based bioengineering plastic and a preparation method and application thereof. The cellulose-polyacrylamide supramolecular gel provided by the present invention has excellent mechanical properties, and after being shaped by organic solvent replacement, drying can obtain a light, high-strength, thermally stable, reproducibly shaped, and biodegradable cellulose-based bioengineering plastic.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a cellulose-based bioengineering plastic, comprising the following steps:

[0007] Mixing cellulose with a mixed aqueous solution of formic acid and zinc chloride to dissolve and esterify the cellulose to obtain a cellulose formate solution;

[0008] The cellulose formate solution is mixed with a metal ion source solution, and complexation self-assembly, organic solvent regeneration and water replacement are performed in sequence to obtain a cellulose formate hydrogel skeleton;

[0009] placing the cellulose formate hydrogel skeleton in an acrylamide aqueous solution for infiltration, and then performing a polymerization reaction to obtain a cellulose-polyacrylamide supramolecular gel;

[0010] The cellulose-polyacrylamide supramolecular gel is subjected to organic solvent replacement and shaping and then dried to obtain a cellulose-based bioengineering plastic.

[0011] Preferably, the molar ratio of formic acid to zinc chloride in the formic acid-zinc chloride mixed aqueous solution is 1:0.25-1, and the molar ratio of formic acid to water is 1:0.5-2;

[0012] The mass ratio of the cellulose to the formic acid-zinc chloride mixed aqueous solution is 1 to 9:100;

[0013] The dissolution-esterification temperature is room temperature, and the time is 1 to 4 hours.

[0014] Preferably, the mass concentration of the metal ion source solution is 30-45%; the metal ions in the metal ion source solution include one or more of calcium ions, iron ions, aluminum ions and lithium ions;

[0015] The temperature of the complex self-assembly is room temperature, and the time is 2 to 10 hours;

[0016] The organic solvent used for the organic solvent regeneration includes one or more of ethanol, methanol, acetone, acetonitrile and tetrahydrofuran; the temperature of the organic solvent regeneration is room temperature, and the time is 4 to 8 hours;

[0017] The water replacement is carried out at room temperature for 2 to 4 hours.

[0018] Preferably, the mass concentration of the acrylamide aqueous solution is 5 to 16 wt %;

[0019] The mass volume ratio of cellulose formate to acrylamide aqueous solution in the cellulose formate solution is 1 g: 25-100 mL;

[0020] The infiltration temperature is room temperature and the time is 12 to 48 hours;

[0021] The polymerization reaction temperature is 50-60° C. and the reaction time is 6-10 hours.

[0022] Preferably, the organic solvent used in the organic solvent displacement shaping includes one or more of lower alcohols, ketone solvents, nitrile solvents and furan solvents.

[0023] The invention also provides cellulose-based bioengineering plastics obtained by the preparation method.

[0024] The present invention also provides a method for preparing a reversibly shaped cellulose-based bioengineering plastic, comprising the following steps:

[0025] The cellulose-based bioengineering plastic described in the above technical solution is sequentially subjected to water plasticization, organic solvent replacement shaping and drying to obtain a reversibly shaped cellulose-based bioengineering plastic.

[0026] Preferably, the organic solvent used in the organic solvent displacement shaping includes one or more of lower alcohols, ketone solvents, nitrile solvents and furan solvents.

[0027] The invention also provides reversibly shaped cellulose-based bioengineering plastics prepared by the preparation method.

[0028] The present invention also provides the use of the cellulose-based bioengineering plastic described in the above technical solution or the reversibly shaped cellulose-based bioengineering plastic described in the above technical solution in construction engineering materials.

[0029] The present invention provides a method for preparing high-performance cellulose-based bioengineering plastics under mild conditions from the perspective of molecular design. A mixed aqueous solution of formic acid and zinc chloride is used to dissolve cellulose, and the cellulose is esterified to form a cellulose formate solution. After adding a metal ion source solution, the cellulose formate molecules are induced by metal ions to effectively promote the self-assembly of cellulose formate molecules to form a cellulose formate hydrogel skeleton; the cellulose formate hydrogel skeleton is immersed in an acrylamide aqueous solution for displacement and in-situ polymerization to form a cellulose-polyacrylamide supramolecular hydrogel. The cellulose formate hydrogel skeleton prepared by the present invention has a tight molecular network skeleton structure, providing strong mechanical support for the supramolecular network. The present invention uses an organic solvent to regulate the molecular configuration of the cellulose-polyacrylamide supramolecular hydrogel, and the polyacrylamide molecules are tightly wound around the cellulose network through hydrogen bonding, and the shape is solidified. The prepared cellulose-based bioengineering plastic has good formability and can form a cellulose-based bioengineering plastic with a 2D or 3D shape. Moreover, the cellulose-based bioengineering plastic prepared by the present invention has the characteristics of light weight and high performance. The preparation method provided by the present invention has a wide range of raw material sources, a mild processing process and simple equipment requirements, and has the potential for engineering large-scale processing and preparation.

[0030] The cellulose-based bioengineering plastic prepared by the present invention has a strong supramolecular network skeleton and can still maintain a very high tensile strength after multiple cycles of shaping.

[0031] The supramolecular networks in the cellulose-based bioengineering plastics are connected by hydrogen bonds. The present invention utilizes the reversibility of the intermolecular hydrogen bonding effect, immerses the cellulose-based bioengineering plastic in water for plasticization, reshapes it, and then reshapes it through organic solvent replacement, thereby achieving repeated shaping of the cellulose-based bioengineering plastic at room temperature.

[0032] The processing of existing cellulose bioplastics has high energy consumption, complex modification procedures, and difficulty in large-size processing, which hinders the further development of cellulose-based bioplastics. Compared with the existing preparation methods, the present invention forms a homogeneous cellulose formate solution at room temperature, and constructs a lightweight, high-strength, thermally stable, repeatable, and biodegradable cellulose-based bioengineering plastic by inducing cellulose self-assembly through metal ion complexation and regulating the supramolecular network configuration with organic solvents. Cellulose formate not only promotes complexation with metal ions to form a tight molecular connection, but also interacts with polyacrylamide molecules through hydrogen bonds, greatly improving the mechanical strength, thermal stability (>154°C) and plasticity of bioplastics, meeting the use requirements of engineering plastics. Moreover, the molding process adopted by the present invention avoids high-energy consumption processing and shaping processes such as high temperature and high pressure. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The following is a process flow chart for preparing cellulose-based bioengineering plastics;

[0034] Figure 2 This is a large-size (50 cm×35 cm) physical picture of the cellulose-based bioengineering plastic prepared in Example 1;

[0035] Figure 3 The infrared spectra of pulp cellulose, polyacrylamide and the cellulose-based bioengineering plastic prepared in Example 2;

[0036] Figure 4 The actual pictures of the cellulose-based bioengineering plastics prepared in Examples 1 to 4;

[0037] Figure 5 This is a physical picture of the reversible and repeated shaping of the cellulose-based bioengineering plastic prepared in Example 9;

[0038] Figure 6 The tensile stress-strain curves of cellulose-based bioengineering plastics (Example 2, Examples 4 to 6) induced by different metal ions;

[0039] Figure 7 The tensile stress-strain curves of cellulose-based bioengineering plastics (Examples 1-2, Examples 7-8) prepared at different cellulose dissolution concentrations;

[0040] Figure 8The tensile mechanical stress-strain curves of the cellulose-based bioengineering plastics prepared in Example 2 and Comparative Example 1;

[0041] Fig. 9 This is a diagram showing the results of dynamic thermomechanical analysis of the cellulose-based bioengineering plastic prepared in Example 2. DETAILED DESCRIPTION

[0042] The present invention provides a method for preparing a cellulose-based bioengineering plastic, comprising the following steps:

[0043] Mixing cellulose with a mixed aqueous solution of formic acid and zinc chloride, dissolving and esterifying, and obtaining a cellulose formate solution;

[0044] The cellulose formate solution is mixed with a metal ion source solution, and complexation self-assembly, organic solvent regeneration and water replacement are performed in sequence to obtain a cellulose formate hydrogel skeleton;

[0045] placing the cellulose formate hydrogel skeleton in an acrylamide aqueous solution for infiltration, and then performing a polymerization reaction to obtain a cellulose-polyacrylamide supramolecular gel;

[0046] The cellulose-polyacrylamide supramolecular gel is subjected to organic solvent replacement and shaping and then dried to obtain a cellulose-based bioengineering plastic.

[0047] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0048] The invention mixes cellulose with a formic acid-zinc chloride mixed aqueous solution, dissolves and esterifies the mixture, and obtains a cellulose formate solution.

[0049] In the present invention, the cellulose preferably includes one or more of pulp cellulose, bamboo cellulose, cotton cellulose, straw cellulose, flax cellulose, bagasse cellulose and xylose residue cellulose.

[0050] In the present invention, the molar ratio of formic acid to zinc chloride in the formic acid-zinc chloride mixed aqueous solution is preferably 1:0.25-1. In a specific embodiment, the molar ratio of formic acid to zinc chloride in the formic acid-zinc chloride mixed aqueous solution may be 1:0.25, 1:0.5, 1:0.75 or 1:1. In the present invention, the molar ratio of formic acid to water in the formic acid-zinc chloride mixed aqueous solution is preferably 1:0.5-2. In a specific embodiment, the molar ratio of formic acid to water may be 1:0.5, 1:1, 1:1.5 or 1:2.

[0051] In the present invention, the mass ratio of the cellulose to the formic acid-zinc chloride mixed aqueous solution is preferably 1-9:100. In a specific embodiment, the mass ratio of the cellulose to the formic acid-zinc chloride mixed aqueous solution may be 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, 5:100, 5.5:100, 6:100, 6.5:100, 7:100, 7.5:100, 8:100, 8.5:100 or 9:100.

[0052] In the present invention, the dissolution-esterification temperature is preferably room temperature, and the dissolution-esterification time is preferably 1 to 4 hours. In a specific embodiment, the dissolution-esterification time can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0053] After the dissolution-esterification, the present invention preferably further comprises centrifuging and defoaming the cellulose formate solution obtained by the dissolution-esterification to obtain cellulose formate. The present invention has no special limitation on the centrifugal defoaming, and the centrifugal defoaming operation well known to those skilled in the art can be used.

[0054] After obtaining the cellulose formate solution, the present invention mixes the cellulose formate solution with a metal ion source solution, and sequentially performs complex self-assembly, organic solvent regeneration and water replacement to obtain a cellulose formate hydrogel skeleton.

[0055] In the present invention, the mass concentration of the metal ion source solution is preferably 30-45%. In a specific embodiment, the mass concentration of the metal ion source solution can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%. In the present invention, the metal ions in the metal ion source solution preferably include one or more of calcium ions, iron ions, aluminum ions and lithium ions; the metal ion source is preferably a metal salt, and the metal salt preferably includes one or more of calcium salts, iron salts, aluminum salts and lithium salts, and more preferably includes one or more of zinc chloride, calcium chloride, iron chloride, aluminum chloride and lithium chloride. There is no special limitation on the amount of the metal ion source solution in the present invention, and it only needs to be able to immerse the cellulose formate solution.

[0056] In the present invention, the temperature of the complex self-assembly is preferably room temperature, and the time is preferably 2 to 10 hours, and in specific embodiments, it can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours. After adding the metal ion source solution, the cellulose formate molecules are induced by metal ions to effectively promote the self-assembly of cellulose, forming a cellulose formate hydrogel skeleton with a tight molecular network, which significantly improves the tensile strength of the material. Without the induction of metal ions, the cellulose molecules are loosely arranged and have low tensile strength.

[0057] In the present invention, the organic solvent used for the organic solvent regeneration preferably includes one or more of ethanol, methanol, acetone, acetonitrile and tetrahydrofuran. In the present invention, there is no special limitation on the amount of the organic solvent, as long as it can immerse the product after the complexation and self-assembly of cellulose formate. In the present invention, the temperature of the organic solvent regeneration is preferably room temperature, and the time is preferably 4 to 8 hours, and in specific embodiments it can be 4 hours, 5 hours, 6 hours, 7 hours or 8 hours.

[0058] In the present invention, there is no particular limitation on the amount of water used for water replacement, as long as it can immerse the product after the cellulose formate organic solvent regeneration. In the present invention, the temperature of water replacement is preferably room temperature, and the time is preferably 2 to 4 hours, and in specific embodiments, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0059] In the present invention, the organic solvent regeneration and water replacement can also remove the solvent and impurities in the system.

[0060] After obtaining the cellulose formate hydrogel skeleton, the present invention places the cellulose formate hydrogel skeleton in an acrylamide aqueous solution for infiltration, and then performs a polymerization reaction to obtain a cellulose-polyacrylamide supramolecular gel.

[0061] In the present invention, the mass concentration of the acrylamide aqueous solution is preferably 5-16wt%. In a specific embodiment, the mass concentration of the acrylamide aqueous solution can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt% or 16wt%. In the present invention, the mass volume ratio of cellulose formate to acrylamide aqueous solution in the cellulose formate solution is preferably 1g:25-100mL. In a specific implementation, the mass volume ratio of cellulose formate to acrylamide aqueous solution can be 1g:25mL, 1g:30mL, 1g:40mL, 1g:50mL, 1g:60mL, 1g:70mL, 1g:80mL, 1g:90mL or 1g:100mL.

[0062] In the present invention, the penetration temperature is preferably room temperature; the penetration time is preferably 12 to 48 hours. In a specific embodiment, the penetration time can be 12 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours or 48 hours.

[0063] In the present invention, the polymerization preferably includes thermal polymerization; the temperature of the polymerization reaction is preferably 50-60°C, and in a specific embodiment, the temperature of the polymerization reaction can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C; the time of the polymerization reaction is preferably 6-10h, and in a specific embodiment, the time of the polymerization reaction can be 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h or 10h.

[0064] After the cellulose-polyacrylamide supramolecular gel is obtained, the cellulose-polyacrylamide supramolecular gel is subjected to organic solvent replacement and shaping and then dried to obtain cellulose-based bioengineering plastics.

[0065] The present invention preferably places the cellulose-polyacrylamide supramolecular gel in a mold for mold compression shaping, and then performs subsequent organic solvent replacement shaping. In the present invention, the mold compression shaping pressure is preferably 0.1-1MPa. In a specific embodiment, the compression shaping pressure can be 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa or 1MPa. The present invention has no special restrictions on the shape and size of the mold, which can be determined according to actual needs.

[0066] In the present invention, the organic solvent used for the organic solvent displacement shaping preferably includes one or more of lower alcohols, ketone solvents, nitrile solvents and furan solvents, wherein the lower alcohol preferably includes methanol and / or ethanol; the ketone solvent preferably includes acetone; the nitrile solvent preferably includes acetonitrile; the furan solvent preferably includes tetrahydrofuran. The present invention has no particular limitation on the amount of the organic solvent, as long as it can immerse the cellulose-polyacrylamide supramolecular gel.

[0067] In the present invention, the temperature of the organic solvent replacement setting is preferably room temperature, and the time of the organic solvent replacement setting is preferably 2 to 6 hours. In a specific embodiment, the time of the organic solvent replacement setting can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0068] In the process of the organic solvent gradually replacing water molecules in the cellulose-polyacrylamide supramolecular hydrogel network, the polyacrylamide molecular configuration curls and entangles with the cellulose molecules, increasing the molecular hydrogen bonding between cellulose and polyacrylamide and increasing the rigidity of the supramolecular network. Therefore, the cellulose-polyacrylamide supramolecular gel is pre-shaped in water and immersed in an organic solvent solution to fix the shape. After removing the organic solvent, a cellulose-based bioengineering plastic with a stable 2D or 3D shape can be obtained.

[0069] In the present invention, the drying temperature is preferably 20-80°C, and in specific embodiments can be 20°C, 25°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C; the present invention has no special limitation on the drying time, and drying to constant weight is sufficient.

[0070] The current problems faced by cellulose bioplastic processing include limited solubility and processability, high modification process cost and easy degradation, resulting in insufficient mechanical properties and thermal stability of cellulose-based bioplastics, and the molding process is difficult to meet the requirements of complex shapes. In response to these problems, the present invention uses formic acid-zinc chloride mixed aqueous solution to homogeneously modify cellulose, combines metal ion-induced cellulose self-assembly and organic solvents to regulate the supramolecular network configuration, designs and regulates cellulose formate and polyacrylamide composite networks, and provides a method for preparing cellulose bioengineering plastics with mild conditions, low cost and excellent performance, as well as a technology for reversible molding at room temperature, which significantly improves the application potential of cellulose-based bioplastics.

[0071] The present invention also provides a cellulose-based bioengineering plastic obtained by the preparation method described in the above technical solution.

[0072] The processing of existing cellulose bioplastics has high energy consumption, complex modification procedures, and difficulty in large-scale processing, which hinders the further development of cellulose-based bioengineering plastics. The present invention uses mild conditions to prepare cellulose bioengineering plastics, dissolves cellulose at room temperature and simultaneously performs in-situ molecular esterification, forms a robust cellulose skeleton through metal ion-induced self-assembly, and then in-situ polymerizes to form a cellulose-polyacrylamide supramolecular hydrogel network, and finally uses an organic solvent to regulate the supramolecular network configuration, and after drying, forms a cellulose-based bioengineering plastic with light weight, high strength, excellent thermal stability and degradable properties, which significantly improves the application potential of cellulose-based bioplastics.

[0073] The present invention also provides a method for preparing a reversibly shaped cellulose-based bioengineering plastic, comprising the following steps: sequentially subjecting the cellulose-based bioengineering plastic described in the above technical solution to water plasticization, organic solvent replacement shaping and drying to obtain the reversibly shaped cellulose-based bioengineering plastic.

[0074] The present invention has no particular limitation on the amount of water used for water plasticization, as long as it can immerse the cellulose-polyacrylamide supramolecular gel.

[0075] In the present invention, the temperature of the water plasticization is preferably room temperature; the purpose of the water plasticization in the present invention is not particularly limited to the softening time, as long as the cellulose-based bioengineering plastic can be softened. The present invention softens the cellulose-based bioengineering plastic by water plasticization, and is easy to process and shape.

[0076] The present invention preferably places the cellulose-polyacrylamide supramolecular gel obtained by water plasticization in a mold for mold compression shaping, and then performs subsequent organic solvent replacement shaping. In the present invention, the pressure of the mold compression shaping is preferably 0.1-1MPa. In a specific embodiment, the pressure of the compression shaping can be 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa or 1MPa. The present invention has no special restrictions on the shape and size of the mold, which can be determined according to actual needs.

[0077] In the present invention, the organic solvent used for the organic solvent displacement shaping preferably includes one or more of lower alcohols, ketone solvents, nitrile solvents and furan solvents, wherein the lower alcohol preferably includes methanol and / or ethanol; the ketone solvent preferably includes acetone; the nitrile solvent preferably includes acetonitrile; the furan solvent preferably includes tetrahydrofuran. The present invention has no particular limitation on the amount of the organic solvent, as long as it can immerse the cellulose-polyacrylamide supramolecular gel.

[0078] In the present invention, the temperature of the organic solvent replacement setting is preferably room temperature, and the time of the organic solvent replacement setting is preferably 2 to 6 hours. In a specific embodiment, the time of the organic solvent replacement setting can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0079] In the present invention, the drying temperature is preferably 20-80°C, and in specific embodiments can be 20°C, 25°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C; the present invention has no special limitation on the drying time, and drying to constant weight is sufficient.

[0080] Due to the reversibility of hydrogen bonding, the formed cellulose-based bioengineering plastics can be re-preformed by immersing them in water and re-shaped by organic solvents, thus achieving multiple reversible processing and shaping. Cellulose-based bioengineering plastics can be shaped at room temperature by regulating the supramolecular configuration through solvents, and can be shaped multiple times in cycles, thus achieving the recycling of bioplastics and avoiding high energy consumption processing methods.

[0081] The present invention provides a reversibly shaped cellulose-based bioengineering plastic prepared by the preparation method described in the above technical solution.

[0082] The present invention also provides the use of the cellulose-based bioengineering plastics or the reversibly shaped cellulose-based bioengineering plastics described in the above technical solution in building engineering materials. In the present invention, the application is preferably in lightweight building panels, honeycomb panels or automotive interior panels.

[0083] The present invention dissolves and esterifies cellulose at room temperature in a cheap and readily available solvent, first induces molecular self-assembly through metal ions to construct a strong and stable cellulose skeleton, then introduces polyacrylamide through in-situ polymerization, and combines with organic solvent regulation to form a bioplastic with cellulose as the main skeleton, and achieves reversible shaping of cellulose-based bioplastics at room temperature by regulating the supramolecular network configuration through solvents. The present invention gives cellulose-based bioengineering plastics excellent mechanical strength through sophisticated molecular design of cellulose self-assembly while also ensuring the toughness, thermal stability and degradability of the material. In addition, this material prepared by low-cost solvents and green processes reduces energy consumption and carbon emissions, and has broad industrial application prospects in building materials such as lightweight building panels, honeycomb panels and automotive interior panels, and is of great significance in replacing traditional petroleum-based plastics and meeting the demand for engineering plastics.

[0084] In order to further illustrate the present invention, the cellulose-based bioengineering plastics and their preparation methods and applications, and the reversibly shaped cellulose-based bioengineering plastics and their preparation methods and applications provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0085] Example 1

[0086] according to Figure 1 The process flow chart shown is for preparing cellulose-based bioengineering plastics.

[0087] Pulp cellulose was added to a mixed solution of formic acid-zinc chloride-water, stirred at room temperature for 1 hour to obtain a cellulose formate solution, centrifuged to remove bubbles and then flattened, poured into a 40% calcium chloride aqueous solution, self-assembled at room temperature for 4 hours, and then immersed in ethanol for 6 hours of ethanol regeneration at room temperature, and then immersed in water for water replacement for 4 hours to obtain a cellulose formate hydrogel. The cellulose formate hydrogel was immersed in a 12% acrylamide aqueous solution for penetration for 12 hours, and then in situ polymerized at 60°C for 8 hours to obtain a cellulose-polyacrylamide supramolecular gel. The cellulose-polyacrylamide supramolecular gel was immersed in ethanol for ethanol replacement for 2 hours, and dried at room temperature to constant weight to obtain a sheet-like cellulose-based bioengineering plastic. Among them, the molar ratio of formic acid, zinc chloride and water in the formic acid-zinc chloride-water mixed solution was 1:0.5:1, the mass ratio of pulp cellulose to the formic acid-zinc chloride-water mixed solution was 5.26:100, and the mass volume ratio of cellulose formate to the acrylamide aqueous solution was 1g:50mL.

[0088] Figure 2 This is a real picture of the large-size (50 cm×35 cm) cellulose-based bioengineering plastic prepared in Example 1. It can be seen that the cellulose-based bioengineering plastic prepared in the present invention has a wide source of raw materials, a mild processing process and simple equipment requirements, and has the potential for engineering large-size processing and preparation.

[0089] Example 2

[0090] Pulp cellulose was added to a mixed solution of formic acid-zinc chloride-water, stirred at room temperature for 1 hour to obtain a cellulose formate solution, centrifuged to remove bubbles and then spread flat, poured into a 40% calcium chloride aqueous solution, self-assembled at room temperature for 4 hours, and then immersed in ethanol at room temperature for 6 hours for ethanol regeneration, and then immersed in water for water replacement for 4 hours to obtain a cellulose formate hydrogel. The cellulose formate hydrogel was immersed in a 12% acrylamide aqueous solution for 12 hours, and then in situ polymerized at 60°C for 8 hours to obtain a cellulose-polyacrylamide supramolecular gel. The cellulose-polyacrylamide supramolecular gel was placed in the middle of a wavy mold (pressure 0.1-1MPa), immersed in ethanol for ethanol replacement for 2 hours, and dried at room temperature to constant weight to obtain a corrugated cellulose-based bioengineering plastic. The molar ratio of formic acid, zinc chloride and water in the formic acid-zinc chloride-water mixed solution is 1:0.5:1, the mass ratio of pulp cellulose to the formic acid-zinc chloride-water mixed solution is 7.53:100, and the mass volume ratio of cellulose formate to acrylamide aqueous solution is 1 g:50 mL.

[0091] Figure 3The infrared spectra of pulp cellulose, polyacrylamide and cellulose-based bioengineering plastic prepared in Example 2 are shown in Figure 2. Compared with the cellulose raw material, the cellulose-based bioengineering plastic has a higher infrared spectroscopy at 1716 cm -1 The new peak at 1658cm -1 and 1613cm -1 The characteristic peak of -NH2 group of polyacrylamide appears at , indicating that the supramolecular network of cellulose formate and polyacrylamide is successfully formed.

[0092] Reshaping: The corrugated cellulose-based bioengineering plastic is immersed in water for 1 hour to reform the cellulose-polyacrylamide supramolecular gel, immersed in ethanol for replacement for 2 hours, and dried at room temperature for 3 hours to obtain a reshaped sheet of cellulose-based bioengineering plastic. The number of reshaping is 1 to 20 times.

[0093] Example 3

[0094] Pulp cellulose was added to a mixed solution of formic acid-zinc chloride-water, stirred at room temperature for 1 hour to obtain a cellulose formate solution, centrifuged to remove bubbles and then spread flat, poured into a 30% calcium chloride aqueous solution, self-assembled at room temperature for 4 hours, and then immersed in ethanol for 6 hours of ethanol regeneration at room temperature, and then immersed in water for water replacement for 4 hours to obtain a cellulose formate hydrogel. The cellulose formate hydrogel was immersed in a 12% acrylamide aqueous solution for 12 hours, and then in situ polymerized at 60°C for 8 hours to obtain a cellulose-polyacrylamide supramolecular gel. The cellulose-polyacrylamide supramolecular gel was placed in the middle of a semi-honeycomb mold (pressure 0.1-1MPa), immersed in ethanol for ethanol replacement for 2 hours, dried at room temperature to constant weight, and then spliced ​​to obtain a honeycomb cellulose-based bioengineering plastic. The molar ratio of formic acid, zinc chloride and water in the formic acid-zinc chloride-water mixed solution is 1:0.5:1, the mass ratio of pulp cellulose to the formic acid-zinc chloride-water mixed solution is 7.53:100, and the mass volume ratio of cellulose formate to acrylamide aqueous solution is 1 g:50 mL.

[0095] Example 4

[0096] Pulp cellulose was added to a mixed solution of formic acid-zinc chloride-water, stirred at room temperature for 1 hour to obtain a cellulose formate solution, centrifuged to remove bubbles and then spread flat, poured into a 40% lithium chloride aqueous solution, self-assembled at room temperature for 4 hours, and then immersed in ethanol at room temperature for 6 hours for ethanol regeneration, and then immersed in water for water replacement for 4 hours to obtain a cellulose formate hydrogel. The cellulose formate hydrogel was immersed in a 12% acrylamide aqueous solution for 12 hours, and then in situ polymerized at 60°C for 8 hours to obtain a cellulose-polyacrylamide supramolecular gel. The cellulose-polyacrylamide supramolecular gel was placed in the middle of an S-shaped mold (pressure 0.1-1MPa), immersed in ethanol for ethanol replacement for 2 hours, and dried at room temperature to constant weight to obtain an S-shaped cellulose-based bioengineering plastic. The molar ratio of formic acid, zinc chloride and water in the formic acid-zinc chloride-water mixed solution is 1:0.5:1, the mass ratio of pulp cellulose to the formic acid-zinc chloride-water mixed solution is 7.53:100, and the mass volume ratio of cellulose formate to acrylamide aqueous solution is 1 g:50 mL.

[0097] Figure 4 The cellulose-based bioengineering plastics prepared in Examples 1 to 4 are real-life images. It can be seen that after the ethanol is used to regulate the supramolecular configuration for shape solidification, the cellulose-based bioengineering plastics have good formability and can be formed into 2D / 3D shaped materials.

[0098] Example 5

[0099] The cellulose-based bioengineering plastic was prepared according to the method of Example 4, the only difference from Example 4 being that the metal salt solution was an aqueous solution of ferric chloride.

[0100] Example 6

[0101] The cellulose-based bioengineering plastic was prepared according to the method of Example 4, the only difference from Example 4 being that the metal salt solution was an aqueous solution of aluminum chloride.

[0102] Example 7

[0103] The cellulose-based bioengineering plastic was prepared according to the method of Example 2, the only difference from Example 2 being that the mass ratio of pulp cellulose to the formic acid-zinc chloride-water mixed solution was 1.01:100, and the cellulose dissolution concentration was 1 wt %.

[0104] Example 8

[0105] The cellulose-based bioengineering plastic was prepared according to the method of Example 2, the only difference from Example 2 being that the mass ratio of pulp cellulose to the formic acid-zinc chloride-water mixed solution was 3.09:100, and the cellulose dissolution concentration was 3 wt %.

[0106] Comparative Example 1

[0107] The cellulose-based bioengineering plastic was prepared according to the method of Example 2, the only difference from Example 2 being that the metal salt solution was replaced by water.

[0108] Example 9

[0109] Pulp cellulose was added to a mixed solution of formic acid-zinc chloride-water, stirred at room temperature for 1 hour to obtain a cellulose formate solution, centrifuged to remove bubbles and then flattened, poured into a 40% calcium chloride aqueous solution, self-assembled at room temperature for 4 hours, and then immersed in ethanol for 6 hours of ethanol regeneration at room temperature, and then immersed in water for water replacement for 4 hours to obtain a cellulose formate hydrogel. The cellulose formate hydrogel was immersed in a 12% acrylamide aqueous solution for penetration for 12 hours, and then in situ polymerized at 60°C for 8 hours to obtain a cellulose-polyacrylamide supramolecular gel. The cellulose-polyacrylamide supramolecular gel was immersed in ethanol for ethanol replacement for 2 hours, and dried at room temperature to constant weight to obtain a sheet-like cellulose-based bioengineering plastic. Among them, the molar ratio of formic acid, zinc chloride and water in the formic acid-zinc chloride-water mixed solution was 1:2:2, the mass ratio of pulp cellulose to the formic acid-zinc chloride-water mixed solution was 7.53:100, and the mass volume ratio of cellulose formate to acrylamide aqueous solution was 1g:50mL.

[0110] The sheet-like cellulose-based bioengineering plastic was immersed in water for 1 hour to reform the cellulose-polyacrylamide supramolecular gel, placed in a spiral-shaped mold, immersed in ethanol for replacement for 2 hours, and dried at room temperature for 3 hours to obtain the reshaped spiral cellulose-based bioengineering plastic.

[0111] The spiral cellulose-based bioengineering plastic was immersed in water for 1 hour to reform the cellulose-polyacrylamide supramolecular gel, placed in the middle of the serrated mold, immersed in ethanol for replacement for 2 hours, and dried at room temperature for 2 hours to obtain the reshaped serrated cellulose-based bioengineering plastic.

[0112] Figure 5 This is a physical picture of the reversible and repeated shaping of the cellulose-based bioengineering plastic prepared in Example 9. It can be seen that since the supramolecular networks are connected by hydrogen bonds, the cellulose-based bioengineering plastic can be plasticized by water molecules and then reshaped by ethanol. This shows that the cellulose-based bioengineering plastic prepared by the present invention has good reproducible shaping properties.

[0113] Test Example 1

[0114] Test method:

[0115] Dissolved cellulose concentration = cellulose mass / (cellulose mass+solvent mass)×100%.

[0116] Concentration of metal salt solution = mass of metal salt / (mass of metal salt+mass of water)×100%.

[0117] Tensile strength test: The tensile strength was tested using an AI-7000s universal mechanical testing machine. The sample size was measured using a vernier caliper and a thickness gauge. The sample was loaded at a constant test speed of 20 mm / min until it broke, and the stress-strain curve was obtained.

[0118] The performance test results of the cellulose-based bioengineering plastics prepared in the examples and comparative examples are shown in Tables 1 and Figure 6 to Figure 9 .

[0119] Table 1 Performance test results of cellulose-based bioengineering plastics prepared in Examples and Comparative Examples

[0120]

[0121] Figure 6 The tensile stress-strain curves of cellulose-based bioengineering plastics (Example 2, Examples 4-6) induced by different metal ions. Figure 6 As shown in Table 1, different metal ions can induce cellulose self-assembly to form cellulose-based bioengineering plastics with different mechanical properties.

[0122] Figure 7 The tensile stress-strain curves of cellulose-based bioengineering plastics (Examples 1-2, Examples 7-8) prepared at different cellulose dissolution concentrations. Figure 7 As shown in Table 1, the cellulose formate hydrogel skeleton provides strong mechanical support for the supramolecular network, giving the cellulose-based bioengineering plastics high strength, so that its tensile strength can exceed 110 MPa.

[0123] Figure 8 The tensile mechanical stress-strain curves of the cellulose-based bioengineering plastics prepared in Example 2 and Comparative Example 1 are shown in FIG. Figure 8 As shown in Table 1, without metal ion induction, the cellulose molecules are loosely arranged and the tensile strength of the material is only 15.4 MPa. However, the cellulose-based bioengineering plastics induced by metal ions have a tight molecular network skeleton and the tensile strength can reach 111 MPa.

[0124] As can be seen from Table 1, cellulose-based bioengineering plastics have a strong supramolecular network skeleton and can still maintain tensile mechanical properties of >83.5MPa after multiple cycles of shaping.

[0125] Fig. 9 This is a diagram showing the results of dynamic thermomechanical analysis of the cellulose-based bioengineering plastic prepared in Example 2. Fig. 9 It can be seen that the thermal stability of cellulose-based bioengineering plastics can reach 154.2℃.

[0126] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a cellulose-based bioengineering plastic, characterized in that: The following steps are involved: Mixing cellulose with a mixed aqueous solution of formic acid and zinc chloride to dissolve and esterify the cellulose to obtain a cellulose formate solution; The cellulose formate solution is mixed with a metal ion source solution, and complexation self-assembly, organic solvent regeneration and water replacement are performed in sequence to obtain a cellulose formate hydrogel skeleton; placing the cellulose formate hydrogel skeleton in an acrylamide aqueous solution for infiltration, and then performing a polymerization reaction to obtain a cellulose-polyacrylamide supramolecular gel; The cellulose-polyacrylamide supramolecular gel is subjected to organic solvent replacement and shaping and then dried to obtain a cellulose-based bioengineering plastic.

2. The preparation method according to claim 1, characterized in that: The molar ratio of formic acid to zinc chloride in the formic acid-zinc chloride mixed aqueous solution is 1:0.25-1, and the molar ratio of formic acid to water is 1:0.5-2; The mass ratio of the cellulose to the formic acid-zinc chloride mixed aqueous solution is 1 to 9:100; The dissolution-esterification temperature is room temperature, and the time is 1 to 4 hours.

3. The preparation method according to claim 1, characterized in that: The mass concentration of the metal ion source solution is 30-45%; the metal ions in the metal ion source solution include one or more of calcium ions, iron ions, aluminum ions and lithium ions; The temperature of the complex self-assembly is room temperature, and the time is 2 to 10 hours; The organic solvent used for the organic solvent regeneration includes one or more of ethanol, methanol, acetone, acetonitrile and tetrahydrofuran; the temperature of the organic solvent regeneration is room temperature, and the time is 4 to 8 hours; The water replacement is carried out at room temperature for 2 to 4 hours.

4. The preparation method according to claim 1, characterized in that: The mass concentration of the acrylamide aqueous solution is 5 to 16 wt %; The mass volume ratio of cellulose formate to acrylamide aqueous solution in the cellulose formate solution is 1 g: 25-100 mL; The infiltration temperature is room temperature and the time is 12 to 48 hours; The polymerization reaction temperature is 50-60° C. and the reaction time is 6-10 hours.

5. The preparation method according to claim 1, characterized in that: The organic solvent used in the organic solvent replacement shaping process includes one or more of lower alcohols, ketone solvents, nitrile solvents and furan solvents.

6. The cellulose-based bioengineering plastic obtained by the preparation method according to any one of claims 1 to 5.

7. A method for preparing a reversibly shaped cellulose-based bioengineering plastic, comprising the following steps: The cellulose-based bioengineering plastic according to claim 6 is sequentially subjected to water plasticization, organic solvent replacement shaping and drying to obtain a reversibly shaped cellulose-based bioengineering plastic.

8. The preparation method according to claim 7, characterized in that: The organic solvent used in the organic solvent replacement shaping process includes one or more of lower alcohols, ketone solvents, nitrile solvents and furan solvents.

9. The reversibly shaped cellulose-based bioengineering plastic obtained by the preparation method of claim 8.

10. Use of the cellulose-based bioengineering plastic according to claim 6 or the reversibly shaped cellulose-based bioengineering plastic according to claim 9 in construction engineering materials.

Citation Information

Cited By

  • Method for preparing cellulose solution or cellulose material through normal-temperature hydrogen bond pre-reconstruction

    CN120757804A